2021
DOI: 10.1128/aem.01730-21
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Multifunctional Arabinofuranosidase/Endoxylanase/β-Xylosidase GH43 Enzyme from Paenibacillus curdlanolyticus B-6 and Its Synergistic Action To Produce Arabinose and Xylose from Cereal Arabinoxylan

Abstract: The PcAxy43B is a modular protein comprising a catalytic domain of glycoside hydrolase family 43 (GH43), a family 6 carbohydrate-binding module (CBM6) and a family 36 carbohydrate-binding module (CBM36) and found to be a novel multifunctional xylanolytic enzyme from Paenibacillus curdlanolyticus B-6. This enzyme exhibited α-L-arabinofuranosidase, endo-xylanase and β-D-xylosidase activities. α-L-Arabinofuranosidase of PcAxy43B revealed the new property of GH43, which released arabinose f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…Genomic data for strain SP3-1 also show a gene encoding for CBM. CBM is reported to assist in the binding of enzymes to insoluble substrates to promote the efficient degradation of cellulosic substrates ( Limsakul et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Genomic data for strain SP3-1 also show a gene encoding for CBM. CBM is reported to assist in the binding of enzymes to insoluble substrates to promote the efficient degradation of cellulosic substrates ( Limsakul et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Prior researches showed that combining hydrolytic enzymes was a beneficial strategy for enhancing sugar releases at a low cost (Taylor et al, 2006;Canakei et al, 2007;Morana et al, 2007;Limsakul et al, 2021). Synergic action was often assessed because the combined effect was greater than the sum of the individual effects.…”
Section: Discussionmentioning
confidence: 99%
“…CAZy classified arabinofuranosidases in seven distinct glycoside hydrolase families (GH 1,3,10,43,51,54,and 62), for knowing their structural and mechanical activities and evolutionary relationship according to the similarities of their protein sequences (Limsakul et al, 2021). Compared with most active catalytically potent xylosidases, GH 43 is categorized into GH-F clan for having no transglycosylation activity (Jordan and Li, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, Abfs specifically catalyze the hydrolysis of α-1,2, α-1,3, α-1,5 glycosidic bonds involving L-arabinofuranosyl residues [ 62 ]. In the CAZy database, the Abfs belong to the Glycosyl Hydrolase (GH) families 2, 3, 10, 43, 51, 54, and 62 [ 63 ]. Various arabinofuranosidases have been identified in several plants, fungi and bacteria, providing useful information for enzymatic characterization.…”
Section: New Challenges For Biocatalysts and The Circular Economymentioning
confidence: 99%
“…Additionally, the multifunctional enzymes are important, such as GH43 α-L-arabinofuranosidase/endoxylanase/β-D-xylosidase. In particular, Paenibacillus curdlanolyticus B-6 produced PcAxy43B, is capable of releasing arabinose, xylose, and XOSs from the arabinoxylan [ 63 ].…”
Section: New Challenges For Biocatalysts and The Circular Economymentioning
confidence: 99%